Whipple's disease in renal transplant recipients: Management experience of seven cases from Pakistan. Issue 1 (14th December 2021) - Nasim, Asma; Dodani, Sunil Kumar; Badlani, Sanjay; Babar, Zaheer Udin; Shakil, Shaheera; Mubarak, Mohammad; Luck, Nasir; Aziz, Tahir
Abstract: Introduction: Whipple's disease (WD) is a rare multi‐systemic disorder caused by actinomycetes, Tropheryma whipplei . It presents with weight loss, arthralgia, and diarrhea and may involve the heart, lung, or central nervous system. The use of immunosuppressive medications or underlying immunodeficiency states are associated risk factors. Six cases in transplant recipients have so far been reported worldwide. We describe our experience of WD in renal transplant recipients. Methods: All renal transplant recipients who presented with diarrhea and were diagnosed with WD on duodenal biopsy from 2016 till 2019 were included. Their data regarding duration since transplantation, immunosuppressive therapy, symptoms, treatment response, and outcome were analyzed. Results: Seven cases were diagnosed as WD based on duodenal biopsy, with histological findings of periodic acid Schiff‐positive granules in macrophages. All were males. The most common symptoms were chronic diarrhea and weight loss. Average time since transplantation was 4.8 years. All patients were on azathioprine and everolimus. Clinical relapse or adverse effects was seen in five of seven patients treated with doxycycline and hydroxychloroquine which was discontinued. Trimethoprim/sulfamethoxazole for 1 year, with initial intravenous ceftriaxone in two patients, resulted in complete remission in all patients at a follow‐up period averaging 1.5 years. Conclusion: WDs in renal transplant recipients most commonly presents as an intestinal disorder. Treatment of 1 year with trimethoprim/sulfamethoxazole has good response with complete remission at 1.5 years of follow up.